ANALISIS EFEKTIVITAS PROGRAM PEMBERDAYAAN USAHA MIKRO, KECIL, DAN MENENGAH MELALUI BELANJA DAERAH DI KOTA KEDIRI - Nasya Firdaushaumy; Anggita Cahyani Setyoningrum; Eva Hany Fanida; Revienda Anita Fitrie (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
Micro, Small, and Medium Enterprises (MSMEs) occupy a strategic position in regional economies, functioning as primary absorbers of labor and drivers of community welfare. Despite the Kediri City Government’s consistent allocation of local government spending toward MSME empowerment programs, studies that specifically examine the linkage between regional expenditure realization and program effectiveness at the local level remain scarce. This study analyzes MSME empowerment program effectiveness through local government spending in Kediri City, employing Dunn’s (2003) program effectiveness framework across three analytical dimensions: output, outcome, and impact. A qualitative approach using library research was applied through thematic analysis of peer-reviewed journals, books, official government reports, and relevant public policy documents. Findings reveal that at the output level, budget realization reached only 82.42%, falling below the optimal threshold; at the outcome level, MSME growth peaked at 34.09% in 2023 before declining sharply in 2024–2025; and at the impact level, Jatim Bejo platform transactions totaling IDR 43.82 billion alongside 3.43% economic growth in 2024 indicate positive but unevenly distributed effects. Enabling factors include local government commitment to budget allocation and digital technology adoption, while key constraints encompass weak inter-agency coordination, limited managerial capacity among MSME actors, and inconsistent monitoring and evaluation mechanisms. This study contributes to the scholarly discourse on fiscal policy effectiveness for local MSME empowerment, and recommends strengthening cross-sectoral coordination, sustained capacity-building assistance for MSME actors, and the development of a more structured data-driven monitoring system. Keywords: Effectiveness; Kediri City; Local Government Spending; Program; SME Empowerment